The immunogenicity and anti-tumor effects of a lung cancer DNA vaccine harboring a MUC-1 and GM-CSF fusion gene - Yang,Zhen (2016)
ABSTRACT DNA vaccines have been shown to be an effective approach to induce antigen-specific cellular and humoral immunity. However, the inability of DNA vaccines to elicit strong immune responses in clinical trials limits the application of DNA vaccines. Here, we developed a new DNA vaccine based on MUC1, which has been suggested as a potential target for lung cancer therapy, and we enhanced the potency of the DNA vaccine by including granulocyte-macrophage colony-stimulating factor (GM-CSF) as an adjuvant. A series of DNA plasmids encoding MUC1, human GM-CSF and their conjugates were constructed and injected into female mice intramuscularly (i.m.). This action was followed by an electric pulse. The humoral and cellular immune responses after immunization were examined by ELISA and ELISPOT, respectively. To evaluate the therapeutic efficacy of the plasmids, a mouse model with a MUC1-expressing tumor was designed. Mice vaccinated with the MUC1-GM-CSF plasmid generated the strongest MUC1-specific humoral and cellular immune responses. Furthermore, these vaccinations inhibited the growth of MUC1-expressing tumors and prolonged mouse survival. These observations emphasize the potential of GM-CSF as an adjuvant for DNA vaccines and of vaccines based on MUC1 and GM-CSF as a promising treatment for lung cancer.